Efecto de la intensidad lumínica de diodos emisores de luz y del fotoperiodo en la producción de forraje verde hidropónico de Maíz (zea mays) y utilización de agua - Fabian Medina, Lenin Vladimir (2017)
Was evaluated the effect of light intensity of Light Emitting Diodes (LED) and photoperiod in the production of hydroponic Green fodder (HGF) of variety corn yellow and use of water, using rotatable central composite design (RCCD) and response surface methodology (RSM). Was used for the production of HGF an adjustable metal support of three (03) levels with centrifugal pump to recirculate the water every two (02) hours for one (01) minute of irrigation by gravity and flood, also two lights LED white and two (02) timers to control the time of the pump operation and the lights. Eleven (11) treatments were performed in trays, with a stocking density of 0.5 g of seeds/cm2 (5 kg/m2). With an additional tray (control) with indirect natural light under shadow. The rest of crops were also placed under indirect natural light under shadow. Eleven (11) treatments were illuminated with LED light during 12 hours of dark. The results showed that there is not proper relationship that allows the use of a statistical model to assess the effect of luminous intensity of light LEDs and photoperiod, in the HGF biomass production of corn. So hydroponic crops with natural lighting is recommended, without changing photoperiod with use light LED white with HGF of corn. Also was determined that there is relationship that allows the use of the statistical model to assess the effect of luminous intensity of light LEDs and photoperiod, in the water consumption for the HGF biomass production of corn. But still important the production of biomass under natural lighting, water consumption was estimated at a production of 1 kg of HGF of corn/1.98 L of water.